2022
DOI: 10.1002/clen.202100407
|View full text |Cite
|
Sign up to set email alerts
|

Integration of Microalgae‐Based Wastewater Bioremediation–Biorefinery Process to Promote Circular Bioeconomy and Sustainability: A Review

Abstract: Bioremediation of wastewater using microalgae is inexpensive, energy efficient, and effective in pollutant reduction as compared to conventional wastewater treatment technologies. Wastewater is a huge resource of minerals, nutrients, bioenergy, and valuable organic compounds and can be used for cultivation of microalgae. The microalgal biomass can be further used as biorefinery feedstock to produce biofuels and commercially important high‐value products. The potential of microalgae toward bioremediation and bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 259 publications
0
0
0
Order By: Relevance
“…In 2016, eribulin's approval was further expanded to include the treatment of patients with advanced liposarcoma, a rare and aggressive form of soft tissue cancer. Clinical trials demonstrated that eribulin improved progression-free survival (the time a patient life without their cancer worsening) compared to a placebo in patients with advanced liposarcoma who had not responded to prior chemotherapy [85].…”
Section: Clinical Trials and The Path To Approvalmentioning
confidence: 99%
“…In 2016, eribulin's approval was further expanded to include the treatment of patients with advanced liposarcoma, a rare and aggressive form of soft tissue cancer. Clinical trials demonstrated that eribulin improved progression-free survival (the time a patient life without their cancer worsening) compared to a placebo in patients with advanced liposarcoma who had not responded to prior chemotherapy [85].…”
Section: Clinical Trials and The Path To Approvalmentioning
confidence: 99%
“…Studies demonstrate microalgae's potential in removing various pollutants from aquaculture wastewater, depending on factors like microalgae species, wastewater load, and supplemental carbon dioxide (Liu et al, 2019). Optimization of cultivation conditions and the selection of appropriate microalgae species are crucial for effective wastewater treatment (Singh et al, 2023). Moreover, the biomass generated during microalgae cultivation can be utilized for biofuel production (Kapoore et al, 2021), animal feed, highvalue compound extraction, and adsorption processes, promoting circular bioeconomy and sustainability (Han et al, 2019;Hawrot-Paw et al, 2019).…”
Section: Microalgae: Bioremediation Nutrient Uptake and Wastewater Tr...mentioning
confidence: 99%